Pengaruh Jumlah Inflasi dan Nilai Tukar terhadap Penyaluran Kredit UMKM Melalui Suku Bunga Dasar Kredit - Sagita Charolina Sihombing; Dina Agnesia Sihombing (Jurnal Manajemen dan Keuangan, 2023)
In this study, a research was conducted to examine how the influence of the amount of inflation and the exchange rate on MSME lending through the Basic Loan Interest Rate. The data used in this study is secondary data obtained from data from Bank Indonesia and BPS RI. The research method is carried out using path analysis with the intervention variable being the basic loan interest rate. Data processing is done with the help of IBM SPSS. The results of this study indicate that inflation has a positive and not significant effect on the prime lending rate, whereas the exchange rate has an insignificant negative effect on the prime lending rate. Inflation and exchange rates have a positive and insignificant effect on total MSME loans, while the SBDK has a significant negative effect on total MSME loans. The prime lending rate does not mediate inflation and exchange rates in influencing MSME credit.